Ebola: In search of a new metaphor. (November 2016) - Kamara, Kewulay
Highlights: ⬢ The importance of storytelling, writ large, in the healing life of a community. ⬢ Indigenous perspectives on health. ⬢ The value of play/performance as a social research tool. ⬢ And in the value of ritual. Abstract: At the Voices Against Ebola, a fund/awareness-raising event held at City Lore Gallery 57 in New York City, I asked participants these questions: What will be the story of Ebola in the year 2064? Will it be the story of one part of humanity experiencing ostracism and stigmatism as evidenced by the walls and barriers constructed against Ebola-affected countries to impede their participation in the life of the global community? Will it be the story of a tragic event in human history that is better forgotten? This piece is a report on the implicit use of CLA in this performance event.